2019
DOI: 10.1371/journal.pone.0221710
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activity of Bulgarian squat. Effects of additional vibration, suspension and unstable surface

Abstract: Practitioners of strength and conditioning are increasingly using vibration and unstable environments to enhance training effects. However, little evidence has been found comparing the use of suspension devices and vibratory platforms used in the Bulgarian squat. The purpose of this cross-sectional study was to examine the effect of suspension devices (TRX ® ), unstable surfaces (BOSU ® ), and vibration plates on muscle activity and force during the Bulgarian squat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
(78 reference statements)
0
19
0
2
Order By: Relevance
“…The effect of additional vibration (30 Hz and 40 Hz with an amplitude of 4 mm) on unstable surfaces and suspension devices increased the demands of the exercise. Thus, eliciting a greater activation of the lower limb muscles (vastus medialis and lateralis, biceps femoris, and gluteus medius) during the suspended lunge combined with 40 Hz WBV than in unstable or suspended exercises without vibration ( Aguilera-Castells et al, 2019 ). Understanding what exercises generate more muscle activation and under what conditions they do so is essential for practitioners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of additional vibration (30 Hz and 40 Hz with an amplitude of 4 mm) on unstable surfaces and suspension devices increased the demands of the exercise. Thus, eliciting a greater activation of the lower limb muscles (vastus medialis and lateralis, biceps femoris, and gluteus medius) during the suspended lunge combined with 40 Hz WBV than in unstable or suspended exercises without vibration ( Aguilera-Castells et al, 2019 ). Understanding what exercises generate more muscle activation and under what conditions they do so is essential for practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Considering acute effects, Bush et al (2015) reported a post-activation potentiation effect on knee extension torque after exposing healthy participants to a WBV dynamic squat with bodyweight resistance (30 Hz and 4 mm of amplitude). Additionally, Aguilera-Castells et al (2019) showed that combined WBV (40 Hz) with a suspended device elicited higher muscle activity than the suspended condition for hip and thigh muscles in the dynamic lunge bodyweight resistance.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, although the BOSU-down condition created higher global instability, it offered a flat and rigid surface that compelled the participants to act differently in avoiding the knee valgus position. Although this study did not test this muscle, the role of the gluteus medius in stabilizing the posture can probably explain the lower activation of the vastus medialis in the BOSU-down [ 13 , 32 , 33 ] actions. Furthermore, the role of the biceps femoris co-contraction in the most unstable conditions seemed to be clear in a half-squat.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, several groups of researchers have studied the acute responses of different unstable environments on muscle activation and force/power production in the past [ 3 , 10 , 13 , 14 ], but to the best of our knowledge, none of them have quantified the amount of instability created. According to the studies’ designs, it can be inferred that some devices can create higher instability than others, but no data are available describing how unstable every condition is.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of the trials was determined based on the preliminary study and the participants' possible fatigue due to the maximum muscle exertion during the exercise task. The participants were given 90-s intervals between each performance for rest [14]. The participants were also instructed to perform the PBM and CIM under the same conditions.…”
Section: Trialsmentioning
confidence: 99%